The Concept of Physical Death from a Christian Perspective: Belief, Hope, and Meaning - H. A Tuan, Yoram; L. Moimau, Aprianus (Theological Journal Kerugma, 2024)
This study aims to explore the concept of physical death from a Christian perspective, focusing on the beliefs, hopes, and meanings associated with it. Using a literature review method, data was gathered from books and articles addressing death within Christian thought. The analysis reveals three significant insights. First, Christian beliefs about physical death include varied understandings of life after death, the relationship between soul and body, and the role of Jesus Christ in death and eternal life. Second, Christian hope regarding physical death encompasses aspects such as the anticipation of heaven, reunion with God, and the immortality of the soul. This hope provides peace and support as Christians approach death, inspiring them to live with purpose and meaning. Third, the meaning of physical death from a Christian perspective includes the understanding of life’s purpose, spiritual preparation, and humanity's role within God’s plan. For Christians, physical death is not viewed as an end but as a transition to a better life. The findings of this study offer deeper insights into how Christian beliefs shape perceptions, hopes, and meanings surrounding physical death. Practical implications of this research can support and guide Christians in confronting mortality.